Efficacy of intravenous ketamine as premedicant for prevention of intraoperative hypotension after spinal anesthesia in parturients posted for elective cesarean section - Manjula BP; Sudeepta Sambrekar; Girish BK (Asian Journal of Medical Sciences, 2023)
Background: Hypotension following spinal anesthesia (SA) in lower segment cesarean section can be deleterious to the parturient and to fetus. Ketamine acts by stimulating the cardiovascular system leading to high blood pressure and increase in heart rate (HR) and cardiac output. Aims and Objectives: This study aimed to assess the efficacy of 15 mg of prophylactic intravenous ketamine in elective cesarean section for prevention of hypotension after SA. Materials and Methods: This double-blinded randomized controlled study was conducted on 98 participating parturients who were American Society of Anesthesiologists term pregnant women. The parturients were randomly divided into two groups (n=49 in each). All the parturients received SA. Ketamine group - Group K received 15 mg of ketamine IV bolus in 3 mL saline and control group - Group C received the same volume of normal saline IV bolus. HR and systolic blood pressure (SBP) were recorded at baseline at 5, 10, 15, and 20 min after the injection and then every 15 min till the end of the operation. Incidences of hypotension were recorded. The total number dose of ephedrine used, APGAR score, and Visual Analog Scale scores were recorded. The Ramsay Sedation Score was also recorded at baseline, then 5, 10, 15, 30, and 45 min after injection, and then at the end of the operation. Results: This study showed a statistically significant increase in the incidence of hypotension and higher use of intravenous ephedrine 6 mg boluses in the control group when compared to the ketamine group. Forty-two parturients in the control group developed hypotension compared to 23 parturients in the ketamine group with P<0.001. The total ephedrine dose was significantly lower among the ketamine group. Sedation was observed for the first 15 min intraoperatively in the ketamine group with P=0.001. There was no statistically significant difference in APGAR score between the two groups. Conclusion: There was significantly higher hemodynamic stability in the ketamine group with regard to SBP, diastolic blood pressure, and HR. Hence, low-dose ketamine, when used as a premedicant, is an effective agent that can be used in preventing post-spinal intraoperative hypotension in parturients undergoing cesarean section delivery.